The role of the church in the #FeesMustFall movement in South Africa: Practical Theological reflection - Kgatle, Mookgo S. (HTS teologiese studies, 2018)
In 2015 and 2016, South Africa experienced one of the unique student-led protests since the dawn of democracy that touched the world, the #FeesMustFall movement. Out of the many demands that the students made in the movement, one is outstanding, fee-free higher education. A large number of publications have been written on the movement from an economical and educational point of view. Most of these publications argue that a fee-free higher education for all students is not an affordable or sustainable option for South Africa at the moment. What is new in this article is a practical theological reflection on the movement in general and the demand for a fee-free higher education by students in particular. The article looks at the possibilities of fee-free higher education for the poor students in South Africa by exploring the roles of the church in the #FeesMustFall movement.